1998
DOI: 10.1046/j.1365-2036.1998.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Ferric trimaltol corrects iron deficiency anaemia in patients intolerant of iron

Abstract: INTRODUCTIONIron de®ciency anaemia is a common haematological problem but current treatment remains unsatisfactory. Intravenous iron supplementation has been withdrawn and intramuscular iron has signi®cant side-effects. Oral iron supplementation, typically with ferrous sulphate, is associated with a high incidence of gastrointestinal sideeffects, 1 and so compliance with treatment is often poor and treatment is ineffective. Although different ferrous preparations are available, there is no signi®cant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 9 publications
3
56
0
1
Order By: Relevance
“…[16] GalliumA C H T U N G T R E N N U N G (III) tris(maltolate) is on clinical trial as an anticancer agent, [17] and has potential as a radiopharmaceutical, [18] and ferric tris(maltolate) has been investigated for the treatment of iron-deficiency anaemia. [19,20] Some reactions of Ru II -arene complexes containing maltolate and similar ligands, for example, ethylmaltolate, have been reported, [21][22][23][24] but not those of their Os (2) containing O,O-chelated maltolate, as well as the acidity of their aqua adducts. Their rates of reaction with guanine and adenine derivatives, and the stabilities of the resulting nucleobase adducts were investigated.…”
Section: [Osa C H T U N G T R E N N U N G (H 6 -P-cym)a C H T U N G Tmentioning
confidence: 97%
“…[16] GalliumA C H T U N G T R E N N U N G (III) tris(maltolate) is on clinical trial as an anticancer agent, [17] and has potential as a radiopharmaceutical, [18] and ferric tris(maltolate) has been investigated for the treatment of iron-deficiency anaemia. [19,20] Some reactions of Ru II -arene complexes containing maltolate and similar ligands, for example, ethylmaltolate, have been reported, [21][22][23][24] but not those of their Os (2) containing O,O-chelated maltolate, as well as the acidity of their aqua adducts. Their rates of reaction with guanine and adenine derivatives, and the stabilities of the resulting nucleobase adducts were investigated.…”
Section: [Osa C H T U N G T R E N N U N G (H 6 -P-cym)a C H T U N G Tmentioning
confidence: 97%
“…Although formal prospective studies do not exist it is generally accepted that Fe deficiency (ID) is common in CD (Gasche et al 1994(Gasche et al , 1997Harvey et al 1998;Mamula et al 2002;Erichsen et al 2003). This is based upon (a) frequent clinical observations; (b) retrospective analysis and audit of patient notes (Child et al 1973;Thomson et al 1978;Gasche et al 1994;De Silva et al 2001a,b;Oldenburg et al 2001); (c) response to oral or intravenous Fe therapy (Gasche et al 1997(Gasche et al , 2001Harvey et al 1998). The latter point is important as anaemia of chronic disease can be difficult to separate from ID but, in a series of carefully controlled studies, Gasche et al (1997Gasche et al ( , 2001) have demonstrated that about 75 % of patients with anaemia and CD respond to Fe therapy leading also to a significant improvement in their quality of life.…”
mentioning
confidence: 99%
“…Some Authors have already demonstrated the superiority of Lactoferrin, compared to ferrous sulfate, in increasing hemoglobin levels in anemic pregnant women and its capacity in increasing ferritin concentrations (18). Lafergin ® also contains 0,002 mg of Vitamin B 12 , which takes part to the development of red blood cells, and 70 mg of Vitamin C that promotes the absorption of iron and protects red blood cells from oxidative stress. Furthermore, the pharmaceutical formulation of Lafergin ® take advantage from a particular and innovative technology (IOR -Improved Oral Release) which guarantees, after a single daily dose supplemented, the maximum bioavailability of its ingredients directly in the bowel for a prompt use by the organism without any side effect.…”
Section: Methodsmentioning
confidence: 99%
“…Basing on these premises, we decided to test the hypothesis that the daily administration of a dietary multicomponent (Lafergin ® ) based on Ferric Sodium EDTA (Ferrazone ® ), Lactoferrin, Vitamin C and Vitamin B 12 , from first trimester of pregnancy until the end of gestation, may significantly reduce, in anemic women, the 3+ (as the one present in Ferrazone ® ) and to transport it through the blood, with a binding-capacity two times higher than transferrin. In this way Lactoferrin is able to control iron homeostasis and contributes to maintain physiological iron concentrations (17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation